The impact of IT governance and data governance on financial and non-financial performance - Hend Mohamed Naguib; Hossam Magdy Kassem; Abd El-Hamed Mostafa Abou Naem (Future Business Journal)
Abstract This paper aims to examine the impact of both information technology governance (ITG) and data governance on information technology (IT) performance in the telecommunication industry. A questionnaire of 308 managers was collected from all telecommunication companies that are working in Egypt. Data were analyzed using smart partial least squares (PLS). The results showed that all the hypotheses of the study had been accepted. IT and data governance have a significant impact on both financial and non-financial performance. However, each of them has a different effect on the IT performance dimensions. The financial performance of IT department had been affected by IT governance more than data governance. Also, innovation and flexibility were the most affected by IT governance. On the other hand, data governance affected business processes and ethical compliance more than IT governance. The current study filled the gap on the literature in two ways. First, studying both IT governance and data governance as a critical factors affects financial and non-financial performance. Second, studying IT governance and data governance has become more important, especially in the telecommunication industry as it is a big challenge now to secure the data of the companies.